(untitled) (Journal of Politica Governo, 2026)
Local governments currently operate within a context of polycrisis characterized by interconnected pandemics, economic instability, climate change, conflict, and migration. This condition requires redefining resilience beyond mere survival toward adaptive and transformative capacities in governance and public policy. This article aims to analyze the main dimensions of local government resilience from political and public policy perspectives using a Systematic Literature Review of studies published between 2021 and 2025. The findings indicate that local resilience rests on four primary pillars: robust institutional capacity, enabling multi-level governance (MLG) and decentralization arrangements, digital transformation and managerial innovation, and social capital with collaborative leadership. Resilience is also shaped by political legitimacy, policy learning, and the availability of internal resources. The study concludes that resilience is not merely an administrative response but an evolutionary process involving learning, cross-sector coordination, and governance transformation. Policy implications highlight the importance of fiscal decentralization, bureaucratic reform, digital public service modernization, and community collaboration in managing multidimensional crises at the local level.